2007
DOI: 10.1590/s1413-70542007000400028
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de tangerina 'poncã' minimamente processada, armazenada a 5°c

Abstract: RESUMOCom o presente trabalho, objetivou-se analisar o comportamento da Tangerina Poncã minimamente processada armazenada a 5ºC. O experimento foi executado no Laboratório de Pós-Colheita de Frutas e Hortaliças do Departamento de Ciência dos Alimentos da Universidade Federal de Lavras MG. As frutas foram lavadas com detergente neutro e sanificadas com hipoclorito de sódio a 200 ppm por 15 minutos, descascadas, embaladas e resfriadas imediatamente a 5ºC. Foi utilizado um delineamento inteiramente casualizado si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Furthermore, these results are in agreement with those found for minimally processed 'Marisol' mandarin (TIBOLA et al, 2006), minimally processed 'Ponkan' mandarin (PINTO; VILAS BOAS; DAMIANI, 2007), minimally processed tangelo 'Minneola' (DEL CARO et al, 2004), and minimally processed 'Pera' orange (ARRUDA et al, 2011). Different behavior profile was observed for the uncoated fruits and those coated with gelatin-based film, in which there was little tendency to TSS TIBOLA et al, 2006;PINTO;VILAS BOAS;DAMIANI, 2007;PLAZA et al, 2011). These losses are related to degradation promoted by oxidative processes stimulated by the presence of light, oxygen, heat, and enzymes such as peroxides and ascorbate oxidase or peroxidase (PLAZA et al, 2006).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, these results are in agreement with those found for minimally processed 'Marisol' mandarin (TIBOLA et al, 2006), minimally processed 'Ponkan' mandarin (PINTO; VILAS BOAS; DAMIANI, 2007), minimally processed tangelo 'Minneola' (DEL CARO et al, 2004), and minimally processed 'Pera' orange (ARRUDA et al, 2011). Different behavior profile was observed for the uncoated fruits and those coated with gelatin-based film, in which there was little tendency to TSS TIBOLA et al, 2006;PINTO;VILAS BOAS;DAMIANI, 2007;PLAZA et al, 2011). These losses are related to degradation promoted by oxidative processes stimulated by the presence of light, oxygen, heat, and enzymes such as peroxides and ascorbate oxidase or peroxidase (PLAZA et al, 2006).…”
Section: Resultssupporting
confidence: 85%
“…According to Kluge and Jorge (1992), the effect of the polyethylene film occurs by maintaining a high relative humidity around the fruit, which minimizes the water vapor pressure deficit and consequently prevents a significant fruit water loss due to transpiration. Pretel et al (1998) and Pinto, Vilas Boas and Damiani (2007) found weight losses below 0.2% for 'Salustiana' citrus fruits peeled and stored in polyethylene film, and maximum loss of 0.3% for 'Ponkan' tangerines peeled and packed in polypropylene plastic container with a lid, respectively.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…For color saturation, the chroma color factor (C), both in the peel and in the inner part of fruits, no interaction was observed between the use of wax coating and time; however, time influenced the behavior of the variable under study (Figure 3 C, D). The chro- ma color factor of the fruit peel, from the 21 st day of storage on, showed decrease in its values from 46.2° to 40.9° on the 36 th day of storage, a result explained by the fact of exposure to oxidative agents is more pronounced in fruit peel, thus accelerating the degradation of these compounds (PINTO et al, 2007). Boonyakiat et al (2012) studied the storage of Ponkan mandarin and found a change in the fruit peel color from green to yellow, and a decrease in chroma values, inferring that such changes occurred due to the oxidative degradation observed in fruits.…”
Section: Postharvest Longevity Of Fremont Iac 543 Mandarin Pacheco Et...mentioning
confidence: 95%